The Role of Prayer in Facing Life's Pressures from a Religious Psychology Perspective - Adi Saputra; Miftahul Jannah; Salami Mahmud (UIN Fatmawati Sukarno Bengkulu, 2026)
Background: This article investigates the role of prayer as a religious coping strategy within an increasingly complex modern world where rapid social changes, competitive work demands, economic instability, and academic pressures create emotional strain requiring effective stress management mechanisms. Understanding how spiritual practices function psychologically becomes essential as unmanaged pressures evolve into chronic stress disrupting mental health.Method: Utilizing a qualitative library research methodology, this study examines primary and secondary literature including scientific journals and books related to spiritual coping and mental health. Data collection involved searching academic databases using keywords such as prayer, religious coping, and mental health, followed by systematic content analysis involving data reduction, presentation, and conclusion drawing with source triangulation for validity.Results: The findings demonstrate that prayer effectively alleviates emotional pressure through multiple psychological mechanisms including focused attention shifting from stress sources to hope, physiological relaxation responses reducing anxiety, reflective processes, and strengthened patience through spiritual surrender. Prayer builds life meaning and hope by connecting individuals with transcendental power while serving as a multidimensional religious coping strategy encompassing emotional management, meaning construction, and community support. Effectiveness varies according to religiosity levels, concentration quality during prayer, social support availability, practice consistency, and integration with complementary psychological interventions.Conclusion: Prayer constitutes an essential mechanism for facing life pressures through complementary psychological and spiritual pathways. It functions as comprehensive emotional regulation that calms thoughts, enhances mental resilience, and fosters hope. Effectiveness depends upon faith depth, devotional quality, and consistent practice. These findings emphasize the importance of holistic approaches integrating psychological and spiritual dimensions for optimal mental health maintenance in modern challenging environments.